Analysis of Tourism Object Potential in Tangerang Regency Based on WebGIS StoryMaps - Mariescha Mega Az Zahra; Putri Desy Ekayanti; Mila Aslamiyah; Adinda Putri Meiliani; Difa Azzahra; Ahman Sya (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose: This study aims to assess the potential of tourist attractions in Tangerang Regency and present them through ArcGIS StoryMaps. Method: The research method used is quantitative descriptive with a spatial approach. The research data was obtained through literature studies, secondary spatial data collection, and visual interpretation using Google Earth and various online sources. The analysis stages were carried out by inventorying and grouping tourist attractions into categories of natural tourism, artificial tourism, and religious tourism, then presenting them spatially through WebGIS StoryMaps. Result: The results showed 14 tourist attractions with diverse characteristics. The presentation through StoryMaps, which combines interactive maps, narration, and visuals, was considered effective as both an analysis medium and a digital promotion tool. Contribution: This research is to provide integrated tourism information and serve as a consideration for local government in planning sustainable tourism development.